2011
DOI: 10.1117/12.881583
|View full text |Cite
|
Sign up to set email alerts
|

Printability of buried mask defects in extreme UV lithography

Abstract: A programmed-defect mask consisting of both bump-and pit-type defects on the LTEM mask substrate has been successfully fabricated. It is seen that pit-type defects are less printable because they are more smoothed out by the employed MLM deposition process. Specifically, all bump-type defects print even at the smallest height split of 1.7 nm whereas pit-type defects print only at the largest depth split of 5.7 nm. At this depth, the largest nonprintable 1D and 2D defect widths are about 23 nm and 64 nm, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the past, several evaluation results of programmed ML defects which were fabricated by e-beam writing and etching process have been reported. 3,4 In these reports, normally the cross-section shape of the programmed defects are rectangle. On the other hand, very curious result are reported that defect printability and defect detectability of rectangular shape programmed defects and natural defects are very different.…”
Section: Introductionmentioning
confidence: 98%
“…In the past, several evaluation results of programmed ML defects which were fabricated by e-beam writing and etching process have been reported. 3,4 In these reports, normally the cross-section shape of the programmed defects are rectangle. On the other hand, very curious result are reported that defect printability and defect detectability of rectangular shape programmed defects and natural defects are very different.…”
Section: Introductionmentioning
confidence: 98%
“…In a previous study [1], defects resulting from bumps and pits programmed in the LTEM substrate were used to find correlation with lithographic results on wafer. Combining the results obtained in that study with existing methods of mitigating EUV native defects [2,3], we propose a novel method which can identify the location of EUV native defects and then shift the layout pattern to avoid their printing on wafer.…”
Section: Introductionmentioning
confidence: 99%